A2.13 Ra-associated autoantibodies promote synovial fibroblast migration and adhesion through a peptidylarginine deiminases (pad) dependent pathway. (24th February 2016) - Sun, M; Joshua, V; Hensvold, AH; Engström, M; Catrina, SB; Ospelt, C; Malmström, V; Amara, K; Wähämaa, H; Rethi, B; Catrina, AI
Abstract : Background and objectives: We have recently demonstrated that anti-citrullinated proteins antibodies (ACPAs) promote IL-8 production and osteoclast activation. In a second step this might lead to chronic synovial inflammation characterised by activation of resident synovial fibroblasts (SF). We aimed to investigate the effect of ACPAs and IL-8 on SF. Methods and materials: SFs were isolated from synovial tissue of RA patients by enzymatic digestion. Polyclonal ACPA and other non-ACPA IgGs were separated from plasma of RA patients by affinity purification on a CCP2 column. Monoclonal ACPAs were generated from synovial fluid single B-cells. Antibodies were tested in migration scratch assays and evaluated by NIH ImageJ software to calculate the migration index in the presence or absence of exogenous IL-8. SF adhesion was analysed by xCELLigence System Real-Time Cell Analyzer (ACEA bioscience). Impedance-based signals were monitored continuously during 36 h. Blocking experiments using phosphoinositide 3-kinase (PI3K), G-protein coupled receptors or focal adhesion kinase (FAK) inhibitors as well as a pan-peptidylarginine deiminases (PAD) inhibitor were performed in the migration scratch assays in the presence or absence of the antibodies. Phosphorylation signal pathways were detected by western blot. Results: Polyclonal ACPAs but not other IgGs induced both SFs migration (a fold increase of 2.6 ± 0.5, mean±SD, p < 0, 05) and SFs adhesion (a fold increase of 1.3 ± 0.1 at 6 h, p < 0.05). Similar effects were observed with two (D10 and B02) out of three tested monoclonal ACPAs, with 2.4 ± 0.4 fold increase of the migration index for D10 antibody and 2.2 ± 0.4 for B02 antibody (p < 0.05 for both). Exogenous added IL-8 had minimal effect on SFs migration, but synergistically promote SF migration in presence of suboptimal ACPAs concentrations. GPCR and PI3K but not FAK blocking completely abolished ACPAs effects. Signalling pathway analysis revealed Akt phosphorylation in SFs in the presence of ACPA. No difference in either cytotoxicity or proliferation rate were observed between different treatments. Conclusion: ACPAs increase SFs migration and adhesion acting synergistically with IL-8. Our ﬁndings suggest that SF might be important players in the ACPA-dependent disease propagation from the bone marrow to synovial tissue.